The Diagonalization Matrix of the ( Z ) p * n   , Where p is an Odd Prime (Journal of the College of Basic Education, 2022)
In this paper we give some concepts that we shall use to determinate the diagonalization of the ( Z ) p*n , where ( Z ) p*n is the tensor product of the matrix of the rational valued character table Zp by itself n-times, p is an odd prime.